Effect of Gibberellin Doses on the Morphologhy of Soybean Strains Infected with Bemisia tabaci - Dyah Kusuma Wardhani; Siti Zubaidah; Heru Kuswantoro (BIOEDUKASI, 2017)
This study aimed to determine the effect giberelin doses on the morphology of several soybeans strains (UM.4-1, UM.7-2, UM.2-4, UM.7-6, UM.6-2 , Gumitir and Wilis) which have been attacked by Bemisia tabaci. Research was conducted at Research Station, Indonesian Legume and Tuber Crops Research Institute, Malang. The design of the study was a complete split plot randomized block design. Spraying gibberellin on 35 days old (35 HST) after-planting soybean with variation dose of giberellin were 0 ppm, 25 ppm, 50 ppm and 75 ppm. Morphological observation was carried out on leaf length, leaf width, leaf area, ratio of leaf, petiole length, leaf shape, color of hipocotyl, rod coat color, the color of ripe pods and flower color. Data were analyzed using 2 ways Anova. The results showed that there was a difference in treatment’s effect against leaf width, leaf ratio, leaf area and petiole length of soybeans but no effect of dose variation on soybean leaf length. There is the effect of the combination treatment (soybean strains and dosage) of the leaf width, leaf ratio, leaf area and petiole soybeans but there is no effect of combination treatment on soybean leaf length. There is the influence of lines on the leaf width, leaf area and ratio, but there is no influence on the long soybean lines of soybean leaf and petiole). Keywords: Gibberelin, Bemisia tabaci, Morphology, Soybean